2014
DOI: 10.1371/journal.pone.0105494
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in Two Seahorse Species (Hippocampus mohnikei and Hippocampus trimaculatus): Evidence for Middle Pleistocene Population Expansion

Abstract: Population genetic of seahorses is confidently influenced by their species-specific ecological requirements and life-history traits. In the present study, partial sequences of mitochondrial cytochrome b (cytb) and control region (CR) were obtained from 50 Hippocampus mohnikei and 92 H. trimaculatus from four zoogeographical zones. A total of 780 base pairs of cytb gene were sequenced to characterize mitochondrial DNA (mtDNA) diversity. The mtDNA marker revealed high haplotype diversity, low nucleotide diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Clear species identification will facilitate augmenting fishing practices, designing protective marine reserves, and assessing the captive breeding potential for seahorses. Our work shows that China has at least 10 species of seahorses along the country's coast; previous studies cited only four: H. kuda, H. mohnikei, H. spinosissimus, and H. trimaculatus (Lin et al, 2006;Lourie et al, 2005;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Clear species identification will facilitate augmenting fishing practices, designing protective marine reserves, and assessing the captive breeding potential for seahorses. Our work shows that China has at least 10 species of seahorses along the country's coast; previous studies cited only four: H. kuda, H. mohnikei, H. spinosissimus, and H. trimaculatus (Lin et al, 2006;Lourie et al, 2005;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 58%
“…Biological mechanisms, water dynamics (such as ocean currents), geographic distance, and historical events may play important roles in the population genetic structures of marine species (Barber et al, 2000;Nelson et al, 2000;Saarman et al, 2010). Many marine fish lack a phylogeographic structure and show genetic homogeneity within populations (Friess and Sedberry, 2011; Zhang et al, 2014). In this study, some intraspecific genetic variations were reduced to 0.15% when comparing individuals from distant localities.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this study, one of the H. trimaculatus specimens possesses a brood pouch, but it was considered as a juvenile since its height was less than 120 mm, according to Yip et al (2015). Although seahorses are not active swimmers, it has been suggested that H. trimaculatus species may have a high dispersal capability and undergo habitat shift or translocation , Zhang et al 2014). The direct observations of H. trimaculatus juveniles near to surface (< 0.1 m) of deep water in this study was likely the first drifting juvenile seahorse ever recorded along Malacca Strait and this could be a strong evidence for the passive long-distance migration in young H. trimaculatus.…”
Section: Discussionmentioning
confidence: 97%
“…Seahorses are known to have wide geographical distributions; however, most populations show low genetic diversity, which is probably because these populations descend from a limited number of founders (Teske et al 2005, Woodall et al 2011, Zhang et al 2014). This phenomenon is probably linked to their poor mobility trait, since all seahorses do not have caudal fins, but do have prehensile tails which allow them to cling on holdfast or bottom substrate (Lourie et al 2004, Curtis andVincent 2006).…”
Section: Introductionmentioning
confidence: 99%